Noninvasive prediction of hepatitis C-associated hepatocellular carcinoma using circulating apolipoproteins - Hasan El Garem; Gamal Esmat; Rabab Salama; Hanan Fouad; Dina Sabry; Yomna Mostafa; Dalia Omran; Heba Omar (SpringerOpen, 2019)
Background and aims Hepatocellular carcinoma (HCC) is one of the leading causes of cancer-related mortality worldwide. We investigated the potential usefulness of circulating apolipoproteins (Apo-A1 and Apo-A4) in HCC screening and diagnosis. Patients and methods We included 60 adult patients with hepatitis C virus-related chronic liver disease including HCC, in addition to 20 healthy controls. Patients were stratified into three equal groups, with 20 patients each: chronic hepatitis C, posthepatitis C cirrhosis (liver cirrhosis), and HCC. All patients and controls underwent full clinical assessment, laboratory investigations, and evaluation of candidate apolipoproteins by enzyme-linked immunoassay. Results Significantly higher Apo-A1 and Apo-A4 levels were detected in patients with HCC than in those with liver cirrhosis (P<0.001). Receiver operator characteristic curve showed that for HCC diagnosis, a cutoff of 78.6 mg/dl for Apo-A1 yielded 90% sensitivity and 100% specificity and a cutoff of 16.5 mg/dl for Apo-A4 yielded 85% sensitivity and 80% specificity. Furthermore, within HCC group, Apo-A1 was significantly higher in patients with small HCC (>2 cm) than those with large tumors (P=0.01). Lower Apo-A1 level correlated significantly with pylethrombosis (P=0.007). Conclusion Apo-A1 and Apo-A4 are novel biomarkers for HCC screening and diagnosis, with a special discriminative ability for Apo-A1 for those with small tumors and those with pylethrombosis.